Path planning of autonomous mobile robots based on Voronoi diagram and ant colony optimization - TUNCER, Adem (Journal of Innovative Engineering and Natural Science, 2023)
Path planning aims to enable autonomous robots to navigate safely and efficiently from a starting point to a target point in challenging and dynamic environments. Path planning in robotics is highly significant and still an ongoing subject of research. The increasing use of robots in various applications such as industrial automation, service robotics, and autonomous vehicles has brought forth the need for reliable and efficient path planning algorithms. The inherent capability of Voronoi diagrams to partition space based on proximity makes them an effective framework for research in path planning. Ant colony optimization, a bio-inspired optimization technique, is based on the foraging behavior of ants and is commonly employed to address the traveling salesman problem and various other combinatorial optimization problems. A hybrid method was adopted in this study by combining a Voronoi diagram and an ant colony algorithm. To create paths for the robot where it can stay as far away from obstacles as possible, a Voronoi diagram was utilized. Additionally, to find the shortest path from the starting point to the destination among these paths, ant colony optimization was employed. The main contribution of the study lies in the combination of the Voronoi diagram for obstacle avoidance and ant colony optimization for finding the optimal path. The combination of these techniques makes an effective contribution to robotic path planning by focusing on ensuring safety by avoiding obstacles while optimizing the shortest path. Experimental studies show that the hybrid method produces successful results for the desired purpose. Yol planlama, zorlu ve dinamik ortamlarda otonom robotların başlangıç noktasından hedef noktasına güvenli ve verimli bir şekilde gitmesini sağlamayı amaçlamaktadır. Robotikte yol planlama oldukça önemlidir ve halen devam eden bir araştırma konusudur. Robotların endüstriyel otomasyon, servis robotiği ve otonom araçlar gibi çeşitli uygulamalarda kullanımının artması, güvenilir ve verimli yol planlama algoritmalarına olan ihtiyacı ortaya çıkarmıştır. Voronoi diyagramlarının uzayı yakınlığa dayalı olarak bölümlendirme konusundaki doğal yeteneği, onları yol planlama araştırmaları için etkili bir çerçeve haline getirmiştir. Biyo-ilhamlı bir optimizasyon tekniği olan karınca kolonisi optimizasyonu, karıncaların yiyecek arama davranışına dayanmakta ve genellikle gezici satıcı problemini ve diğer çeşitli kombinatoryal optimizasyon problemlerini çözmek için kullanılmaktadır. Bu çalışmada Voronoi diyagramı ile karınca kolonisi algoritmasının birleştirilmesiyle hibrit bir yöntem denenmiştir. Robotun engellerden mümkün olduğu kadar uzak durabileceği yollar oluşturmak için Voronoi diyagramı kullanılmıştır. Ayrıca bu yollar arasında başlangıç noktasından hedef noktasına en kısa yolu bulmak için karınca kolonisi optimizasyonundan yararlanılmıştır. Deneysel çalışmalar, Voronoi diyagramının engellerden uzakta oluşturduğu yollar arasında karınca kolonisi optimizasyonu kullanılarak en kısa yolun bulunabileceğini göstermektedir.